Siamois is required for formation of Spemann’s organizer - Kessler, Daniel S. (The National Academy of Sciences of the USA, 1997)
Spemann’s organizer develops in response to dorsal determinants that act via maternal components of the wnt pathway. The function of siamois, a wnt-inducible homeobox gene, in Spemann’s organizer development was examined by fusion of defined transcriptional regulatory domains to the siamois homeodomain. Similar to native siamois, a VP16 activator fusion induced axis formation, indicating that siamois functions as a transcriptional activator in axis induction. Fusion of the engrailed repressor generated a dominant inhibitor that blocked axis induction by Xwnt8, β-catenin, and siamois, and repressed wnt activation of the goosecoid promoter. Dorsal injection of the engrailed-siamois fusion resulted in complete inhibition of dorsal development and organizer gene expression, an effect rescued by siamois, but not by Xwnt8 or β-catenin. Thus, as a zygotic mediator of maternal dorsal signals, siamois function is required for development of Spemann’s organizer.